2020
DOI: 10.1021/acsomega.0c01340
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Novel Collagen Peptides against Platelet Aggregation and Thrombosis from Salmo salar

Abstract: Collagen is a rich source of bioactive peptides and is widely distributed in the skin and bone tissue. In this study, collagen from Salmo salar skin was hydrolyzed with Alcalase or Protamex followed by simulated digestion, YMC ODS-A C18 separation, and ESI-MS/MS analysis. A total of 19 peptides were identified and synthesized for investigation of their antiplatelet activities. Hyp-Gly-Glu-Phe-Gly (OGEFG) and Asp-Glu-Gly-Pro (DEGP) exhibited the most potent activity against ADP-induced pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Notably, the coagulation parameters were not altered when treated with OG‐5 in effective dosage (Figure 1D), which is consistent with the result of tail bleeding assay that OG‐5 (200 µmol kg −1 bw) would not prolong the bleeding time. [ 6 ] These results suggest that OG‐5 effectively inhibits thrombus formation without causing bleeding complication.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Notably, the coagulation parameters were not altered when treated with OG‐5 in effective dosage (Figure 1D), which is consistent with the result of tail bleeding assay that OG‐5 (200 µmol kg −1 bw) would not prolong the bleeding time. [ 6 ] These results suggest that OG‐5 effectively inhibits thrombus formation without causing bleeding complication.…”
Section: Discussionmentioning
confidence: 88%
“…Our previous study also showed that OG‐5 exhibits the most potent activity against ADP‐induced platelet aggregation with IC 50 values of 277.17 µM and inhibits the granule release of β‐TG and 5‐HT. [ 6 ] Antithrombosis ability in vivo of OG‐5 was further evaluated in carrageenan‐induced mouse tail thrombosis model by using aspirin as a positive control. As shown in Figure 1C, OG‐5 inhibited thrombus formation by 30% at an oral dosage of 50 mg kg −1 bw, approximately.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations